Differential response to different classes of herbicides: Tradescantia pallida (Rose) D. R. Hunt var. purpurea Boom as a model plant - Menegazzo, Renato Fernando (2021)
Tradescantia pallida is an ornamental plant widely found in flowerbeds and urban gardens. However, information about the physiological and biochemical responses of this ornamental plant to herbicides is scarce. Therefore, this work aimed to evaluate the toxicity, regrowth capacity, growth, physiology, and alterations in the metabolism of T. pallida after the application of different herbicide classes. The treatments consisted of spraying the herbicides: atrazine (1,500 g ha-1), diquat (300 g ha-1), carfentrazone (10 g ha-1), glyphosate (1,500 g ha-1), and 2,4-D (1,050 g ha-1) on T. pallida. Plants sprayed only with water represented the control group. The evaluations were carried out five days after the application of the herbicides. The evaluated variables were visual toxicity and regrowth index, chlorophyll a fluorescence, chlorophyll content (a, b and a + b), carotenoids and proline content. The herbicide 2,4-D did not act on the plant, but it may have produced a genotoxic effect. Glyphosate significantly increased the proline content and generated zero regrowth index, showing the plant's sensitivity to the herbicide. Carfentrazone was not fully effective in controlling T. pallida, which also did not show sensitivity to atrazine, but high sensitivity to diquat, despite the low proline content found. The different classes of herbicides act differently in terms of toxicity, regrowth, physiology and metabolism of T. pallida, these being useful variables to investigate the possible tolerance of plants to the different classes of herbicides.